Application of the Folin-Ciocalteu method to the evaluation of Salvia sclarea extracts - Nataliia Hudz; Oksana Yezerska; Mariia Shanaida; Vladimira Horčinová Sedláčková; Piotr P. Wieczorek (Pensoft Publishers, 2019)
Polyphenols are valuable group of phytoconstituents due to their high antioxidant activity and healing properties. Antioxidant properties of sages are attributed mainly to a high level of phenolic compounds. The aim of the present study was to elaborate an analytical procedure for the evaluation of the content of secondary metabolites of the polyphenol nature in the herb of Clary Sage (Salvia sclarea L.). Four crude extracts of Salvia sclarea herb obtained with different technologies were used to develop an analytical procedure for the total phenolic content (TPC) assay by spectrophotometric method. The optimum conditions for the analysis (time of the reaction, wavelength, and reference substances) were chosen and experimentally justified (60-80 min, 760 nm, gallic acid and rutin, respectively). Under these conditions, the developed analytical procedure is robust in the indicated time and easy for performing in phytochemical or technological laboratories. The yield of TPC from the herb of Salvia sclarea was the highest in the extracts prepared by heating at a temperature of 36-46 °C and with using the ultrasonic bath. TPC was the highest in the extract in which solvent-to-herb ratio was the least (10:1) and particle size was in the range of 2-5 mm. As a result of the studies, the analytical procedure of the determination of TPC was developed and its parameters were justified. This methodology complies with the requirements for pharmaceutical analysis to ensure the reliability of results during pharmaceutical development and routine control of Salvia sclarea extracts.